Теорема Фрагмена – Ліндельофа для розв'язків еліптичних диференціальних рівнянь у банаховому просторі - Горбачук, М.Л. (Український математичний журнал, 2007)
Для дифференциального уравнения второго порядка эллиптического типа на полуоси в банаховом пространстве показано, что если порядок роста на бесконечности его решения не выше экспоненциального, то это решение экспоненциально стремится к нулю на бесконечности. For a second-order elliptic differential equation considered on the semiaxis in a Banach space, we show that if the order of growth of its solution at infinity is not higher than the exponential order, then this solution exponentially tends to zero at infinity.